2020
DOI: 10.1088/2053-1591/ab8258
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining ultrafine spheroidized carbides by combining warm deformation with divorced eutectoid transformation in GCr15 bearing steel

Abstract: In this work, the ultrafine spheroidized carbides were obtained by combining warm deformation with the divorced eutectoid transformation (DET) in GCr15 bearing steel. The results show that the temperature range of DET is approximately 730°C to 700°C at a cooling rate of 0.05°C s −1 . It is also found that excellent spheroidized microstructure can be obtained and less deformation resistance can be generated when the deformation is carried out at 720°C with a strain rate of 0.5 s −1 . This result could be ascrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Since the deformation can accelerate the DET process and refine the microstructure, some scholars combined DET with warm deformation (WD) to simultaneously realize the SA and shape forming. Our previous work indicated that the fine and uniform spheroidized carbides could be obtained by combining DET and WD in GCr15 steel [17,18]. In addition, Han et al [19,20] investigated the impact of deformation conditions on the spheroidizing process in GCr15, and the optimum deformation temperature was determined at 800 • C with a total reduction of 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Since the deformation can accelerate the DET process and refine the microstructure, some scholars combined DET with warm deformation (WD) to simultaneously realize the SA and shape forming. Our previous work indicated that the fine and uniform spheroidized carbides could be obtained by combining DET and WD in GCr15 steel [17,18]. In addition, Han et al [19,20] investigated the impact of deformation conditions on the spheroidizing process in GCr15, and the optimum deformation temperature was determined at 800 • C with a total reduction of 30%.…”
Section: Introductionmentioning
confidence: 99%